Antecedents and Consequences of Brand Pride: An Investigation of The Causes of Brand Pride and Its Consequences for Willingness to Pay A Premium Price - Tesalonika, Ilona; Susilowati, MG Westri Kekalih (Jurnal Penelitian Ekonomi dan Bisnis, 2023)
In addition to protecting the product, the brand is also a guarantee of quality. Therefore, consumers often pay a premium price for branded goods. In some cases, branded goods also often become status symbols that reflect the prestige that gives brand pride so that consumers will align their brand choice with their self-concept (self-brand congruity). This study investigates the effect of self-brand congruity on willingness to pay a premium price through its impact on brand pride. The study was conducted on Smartphone users with the iPhone brand, a smartphone with a premium price. The study involved 120 respondents with various occupations. The test was carried out using Structural Equation Modeling, which was processed with Smart PLS4.0. The results show that self-brand congruity positively significantly Individual Brand Pride, Collective Brand Pride, and willingness to pay a premium price. Meanwhile, Individual Brand Pride is positively willing to pay premium prices, while collective brand pride does not. Individual Brand Pride is proven as a partial variable mediating the effect of self-brand congruity on willingness to pay a premium price.